Use of European pulses to produce functional beverages – From chickpea and lupin as dairy alternatives. (November 2022) - Duarte, C.M.; Nunes, M.C.; Gojard, P.; Dias, C.; Ferreira, J.; Prista, C.; Noronha, P.; Sousa, I.
Graphical abstract: Highlights: "Beany" volatile compounds extinction after chosen technology processing steps. The impact of the beverage processing step on the flatulence sugars amount. Structural changes of starch induced by thermal processing. Lactic fermentation of chickpea- and lupin- beverages. Time and temperature of fermentation tunning to obtain a yogurt-like gel structure. Abstract: Consumption of plant based products as dairy alternatives is increasing steeply. This diet transition can only be achieved if these products keep the nutritional value and meet consumer's sensory acceptance. This work aimed to evaluate the decrease of the "beany" flavour and of raffinose, stachyose and verbascose contents in EU pulse beveragés production, and also the best lactic fermentation conditions of the beverages, towards chickpea- and lupin-based yoghurts, with rheology properties similar to the commercial soy yoghurts. The reduction of "beany" volatile compounds of chickpea and lupin beverages during processing was confirmed through GC–MS analysis. Soaking and cooking processes were effective in removing flatulence sugars with almost 48% loss from the initial content in lupin beverage. The fermentation conditions at 40 °C, 12 h and 2% (w/v) of starter concentration evidenced the best viscoelastic structure and flow properties. The lupin yoghurt-type showed a similar gel structure to commercial soy yoghurt.